Relationship between Duration of Infant Exposure to a Moderate-to-Large Patent Ductus Arteriosus Shunt and the Risk of Developing Bronchopulmonary Dysplasia or Death Before 36 Weeks - Clyman, Ronald I.; Hills, Nancy K.; Liebowitz, Melissa; Johng, Sandy (American Journal of Perinatology, 2020)
Objective This study was aimed to examine the relationship between duration of infant exposure to a moderate-to-large patent ductus arteriosus (PDA) shunt and the risk of developing bronchopulmonary dysplasia (BPD) or death before 36 weeks (BPD/death).Study Design Infants <28 weeks' gestation who survived ≥7 days (n = 423) had echocardiograms performed on day 7 and at planned intervals.Results In multivariable regression models, BPD/death did not appear to be increased until infants had been exposed to a moderate-to-large PDA for at least 7–13 days: OR (95%CI) (referent = closed or small PDA): moderate-to-large PDA exposure for <7 days: 0.38 (range, 0.10–1.46); for 7 to 13 days = 2.12 (range, 1.04–4.32); for ≥14 days = 3.86 (range, 2.15–6.96). Once the threshold of 7 to 13 days had been reached, additional exposure (≥14 days) did not significantly add to the increased incidence of BPD/death: (referent exposure = 7–13 days) exposure for 14 to 27 days = 1.34 (range, 0.52–3.45); for 28 to 48 days = 2.34 (range, 0.88–6.19); for ≥49 days = 1.80 (range. 0.59–5.47). A similar relationship was found for the outcome of BPD-alone.Conclusion Infants < 28 weeks' gestation required at least 7 to 13 days of exposure to a moderate-to-large PDA before a significant increase in the incidence of BPD/death was apparent. Once this threshold was reached additional exposure to a moderate-to-large PDA did not significantly add to the increased incidence of BPD/death.
Keywords: ductus arteriosus; bronchopulmonary dysplasia; death; extremely low gestational age infants